Impact of Inflation and the Rupiah Exchange Rate on Stock Returns in Indonesia: Evidence from Monthly Data (2020–2024) - Aurel Dafina Rezka Firdaus; Suhono Suhono; Liya Megawati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study examines the effect of inflation and the rupiah exchange rate on stock returns in the Indonesian stock market during the period January 2020 to December 2024. Methodology: This study employed a quantitative explanatory design using monthly secondary data obtained from Bank Indonesia (BI) and the Central Statistics Agency (BPS). The data were analysed using multiple linear regression with SPSS version 26. Results: The results indicate that inflation and the rupiah exchange rate do not have a significant effect on stock returns, either partially or simultaneously. The coefficient of determination (R²) of 0.055 shows that inflation and the exchange rate explain only 5.5% of the variation in stock returns, while the remaining 94.5% is explained by other factors outside the model. Findings: These findings suggest that stock return movements in Indonesia during the post-COVID-19 period are driven primarily by variables beyond inflation and exchange rate dynamics. Novelty & Originality: This study offers novelty by examining the post-pandemic period (2020–2024), a unique economic recovery phase rarely explored in prior research on macroeconomic determinants of stock returns in Indonesia. Conclusions: The study concludes that investors should consider other macroeconomic and firm-specific factors beyond inflation and exchange rates. Type of Paper: This paper is an empirical research paper.